(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Water is a vital resource for all kinds of lives. Heavy metals (HM) generally enter the aquatic environment through natural (atmospheric deposition, erosion of geological matrix) or anthropogenic activities caused by industrial effluent, domestic sewage, mining and agricultural wastes. Tanning generally requires using a heavy chemical that contains chromium, cadmium etc. It was observed that these industrial wastes are discharged, without proper treatment, into small waterways, which subsequently adjoin the rivers and dams. Using agricultural chemicals and fertilizers also contributes to the chemical contamination of the aquatic environment. Discharging untreated sewage into the waterways introduce pathogenic microorganism into the marine environment, among other reasons, which has drawn the attention of researchers to the possibility of having the aquatic organism edible by humans (mostly fish) be contaminated by heavy metals and microorganisms, which have been confirmed to cause short- and long-term health hazards. Fish, one of the primary aquatic organisms in the food chain, may often accumulate large amounts of metals, which can later intoxicate humans after consumption. Humans can also be intoxicated by directly consuming untreated water contaminated with heavy metals. This review focused on the aquatic contamination of different heavy metals in water and fish and also suggested some recommendations to minimize the marine environment’s toxicity.